Asymptomatic carotid artery stenosis: who should be screened, who should be treated and how should we treat them? - de Waard, D; Morris, D; de Borst, G; Bulbulia, R; Halliday, A (Edizioni Minerva Medica, 2017)
Although stopping smoking, lowering blood pressure and reducing lipid levels will reduce global stroke risk and cardiovascular mortality, these remain leading causes of death and disability especially in ageing populations. Further prevention strategies are needed and, in the first part of this review, we explore the potential benefits of appropriate screening for carotid artery disease to reduce stroke and identify those who may have related cardiac disease. Although whole-population carotid screening is an inefficient and costly means of identifying candidates with tight carotid stenosis who might warrant intervention, it can identify many people with lower levels of stenosis who may benefit from cardiovascular risk-reducing medications. Longer-term benefits and cost-effectiveness of any targeted screening program needs further evaluation. Patients with carotid stenosis are known to be at increased risk of stroke and vascular death. Whilst randomized clinical trials and guidelines have reported stroke hazards and benefits of interventional treatment for carotid stenosis, uncertainty remains about their optimal medical management. In the second part of this review we discuss Level I evidence for medical and surgical treatment of asymptomatic carotid stenosis, reasons for the current lack of consensus on interventional management of these patients and future studies which may help to clarify which groups will (and which will likely not) benefit from interventions.